2014
DOI: 10.1215/00127094-2410176
|View full text |Cite
|
Sign up to set email alerts
|

A density version of the Vinogradov three primes theorem

Abstract: We prove that if A is a subset of the primes, and the lower density of A in the primes is larger than 5/8, then all sufficiently large odd positive integers can be written as the sum of three primes in A. The constant 5/8 in this statement is the best possible.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 13 publications
(33 reference statements)
1
23
0
Order By: Relevance
“…This directly follows by Green's argument (see [19,27]). It is usually applied as follows in studying additive problems involving dense subsets of primes.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…This directly follows by Green's argument (see [19,27]). It is usually applied as follows in studying additive problems involving dense subsets of primes.…”
Section: Introductionmentioning
confidence: 67%
“…https://doi.org/10.1017/fms.2014. 27 We are now ready to prove Theorem 4.1. Let R = N 1−δ/2 and Q = N δ/4 be parameters.…”
Section: Proof Of Vinogradov's Theoremmentioning
confidence: 95%
See 1 more Smart Citation
“…then for every sufficiently large odd integer n, there exist p i ∈ P i (i = 1, 2, 3) such that n = p 1 + p 2 + p 3 . Motivated by the work of Li and Pan, X. Shao proved [5] (2014) that if A is a subset of P with δ(A) > 5 8 , then for every sufficiently large odd integer n, there exist p i ∈ A (i = 1, 2, 3) such that n = p 1 + p 2 + p 3 . It is worth mentioning that X. Shao gave [6] (2014) an l-function-free proof of Vinogradov's three primes theorem.…”
Section: Introductionmentioning
confidence: 99%
“…This is sharp in the sense that there are examples in which α 1 + α 2 + α 3 = 2 but the claim is not true. However X. Shao [15] has very recently shown that in case P 1 = P 2 = P 3 it is enough that α i > 5/8 (which is again sharp).…”
Section: Introductionmentioning
confidence: 99%